Teachers' Perspectives towards Strategies for Promoting Self-Regulated Learning in Secondary Classes in Sri Lanka - Safeek, N.M.M.; Nawastheen, F.M. (Indian Sociological Society (ISS), 2025)
This study explores secondary school teachers' perceptions and approaches to fostering selfregulated learning (SRL) in Sri Lanka. It aims to evaluate teachers' understanding of SRL. The following objectives were formulated: to identify the strategies and technologies they used, assess the perceived effectiveness of these methods, and examine the challenges in promoting SRL.A structured online survey was conducted with 440 teachers. These teachers were from Sinhala, Tamil, and English mediums across diverse school types. The survey collected both quantitative and qualitative data. Results indicate that teachers widely acknowledge the significance of SRL. They agree on its teachability and relevance across subjects. However, there is uncertainty about students' inherent self-regulation capabilities. Variations in strategy use were observed among different mediums. English medium teachers expressed the highest level of agreement. A positive link was found between teacher’s confidence in SRL strategies and their perceived effectiveness. Key challenges include limited resources and time constraints. Socio-economic factors also impact student motivation. The study concludes that while teachers hold favorable views on SRL, its implementation faces significant obstacles. Practical recommendations include prioritizing teacher training, enhancing resource distribution, and encouraging collaboration among educators. Future research should investigate the long-term effects of SRL initiatives and explore the influence of parental involvement. Addressing these barriers could strengthen SRL practices in Sri Lanka, which could lead to improved academic performance for students.
Keywords: teachers' perceptions; strategies; self-regulated learning; secondary classes